Members’ Perceived Performance of an Agriculture Cooperative in Nepal: A Case of the Devisthan Agriculture Cooperative Limited in Pokhara, Nepal - Pasa, Rajan Binayek; Regmi, Bhawana; Adhikari, Devendra (Dhaulagiri Journal of Sociology and Anthropology, 2024)
Cooperatives are associations of people who voluntarily cooperate for mutual socio-economic and cultural benefits. It is important to understand the performance of cooperatives as perceived by their members, which would be crucial to sustaining a cooperative in the future. However, there is limited research that unpacks members’ perceived performance of the cooperatives in the Nepalese context. This study (a) assesses the perceived performance of the board members and general members of the Devisthan Agriculture Cooperative Limited (DACL), and (b) examines if the perceived performance varies by members’ characteristics. We used a self-administered questionnaire to collect data from 138 randomly sampled respondents who were members of the DACL. The survey included five indicators to measure performance: relevancy, efficiency, effectiveness, impact, and sustainability. Both descriptive and inferential statistical tools were used for analysis. Findings showed that the perceived performance of the members on various indicators of performance significantly varied. The characteristics -respondents’ category, sex group, caste/ethnicity, involvement in business, formal education, and participation in capacity and skill development training — were among the significant predictors influencing performance. Implications for enhancing the performance of agriculture cooperatives have been discussed.